2020
DOI: 10.1002/adma.202004804
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Strategy for Studying Biochemical Pathways in Double Emulsion Templated Cell‐Sized Compartments

Abstract: optimize these pathways and thus to guarantee their maximum chance of survival, cells produce enzymes at precise and constant rates. [4] However, because of cellular complexity, determination of optimal enzyme levels is still unclear, in particular because specific enzymatic functions are strongly interconnected with their cascade effects. [5] A smart manner to study the behavior of enzymes, when involved in complex reactions, consists of taking advantage of synthetic micrometer-sized compartments shaped into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 80 publications
(133 reference statements)
1
68
0
Order By: Relevance
“…Similarly, such interaction was seen with the related horseradish peroxidase, 45 and recently reported for LPO in giant unilamellar vesicles as well. 44 The vesicular architecture of LPO-and GOX CNCs was conrmed by TEM micrographs revealing the deformed spherical morphology typical of this kind of polymersome (Fig. 2A, B and S1 †).…”
Section: Generation and Characterization Of Catalytic Nanocompartmentsmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, such interaction was seen with the related horseradish peroxidase, 45 and recently reported for LPO in giant unilamellar vesicles as well. 44 The vesicular architecture of LPO-and GOX CNCs was conrmed by TEM micrographs revealing the deformed spherical morphology typical of this kind of polymersome (Fig. 2A, B and S1 †).…”
Section: Generation and Characterization Of Catalytic Nanocompartmentsmentioning
confidence: 92%
“…polymersomes and other cell-mimics, but never in colloidal vesicle networks. 44,56 In a previous study we had showed that in the case of un-clustered CNCs, inter-polymersome distances above 1.5 mm signicantly hinder the cascade reaction due to the slow diffusion of the "bridging" molecule (the product of the rst reaction that is released from the rst type of CNC and serves as substrate for the second reaction inside the second type of CNC). 26 On the contrary, CNC clustering averted this limitation, resulting in a considerably increased reaction rate at a constant amount of encapsulated enzymes.…”
Section: Cascade Within Clustersmentioning
confidence: 99%
“…Microscopic GUVs were assembled from double emulsion templates created by microfluidics. Water-oil-water double emulsions were generated in a six-way junction microfluidic chip, 22 with defined flow rates using a three-module precision syringe pump (low pressure NEMESYS, Cetoni, Germany). PBS containing 20 wt/v% poly(ethylene glycol) (PEG, 3000 Da) and 300 mM sucrose was used as inner aqueous phase (IA).…”
Section: Formation Of Suvs and Guvsmentioning
confidence: 99%
“…Live imaging of this process was followed using a high-speed digital microscope (Meros, Dolomite). In order to evaporate the organic solvents from the double emulsions and thus form a vesicular bilayer membrane according to an established protocol, 22 198 μL of a double emulsion sample and 2 μL of a 100 μM aqueous BODIPY 630/650 solution were transferred into a Nunc Lab-Tek eight-well chamber plate (Thermo Fisher Scientific, USA) and incubated at room temperature for 20 min. Within this time, GUVs were created from double emulsions, which settled to the bottom of the well for further CLSM imaging.…”
Section: Formation Of Suvs and Guvsmentioning
confidence: 99%
See 1 more Smart Citation